2017
DOI: 10.1117/1.jbo.22.8.086002
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations support non-Cerenkov radioluminescence production in tissue

Abstract: There is experimental evidence for the production of non-Cerenkov radioluminescence in a variety of materials, including tissue. We constructed a Geant4 Monte Carlo simulation of the radiation from P32 and Tc99m interacting in chicken breast and used experimental imaging data to model a scintillation-like emission. The same radioluminescence spectrum is visible from both isotopes and cannot otherwise be explained through fluorescence or filter miscalibration. We conclude that chicken breast has a near-infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Another possible source that has been investigated is radioluminescence light that is normally produced by the interaction of ionizing radiations with a scintillator material. However it has been recently shown that radioluminescence light can also be produced in non scintillating material like: Plexiglas, glass [33] small animals [34] or ex vivo tissue [35]. An alternative solution to solve the problem of light tissue penetration is the use of an external X-rays source in combination with scintillating nanoparticles (ScNPs).…”
Section: Pdt Using Radioluminescence Lightmentioning
confidence: 99%
“…Another possible source that has been investigated is radioluminescence light that is normally produced by the interaction of ionizing radiations with a scintillator material. However it has been recently shown that radioluminescence light can also be produced in non scintillating material like: Plexiglas, glass [33] small animals [34] or ex vivo tissue [35]. An alternative solution to solve the problem of light tissue penetration is the use of an external X-rays source in combination with scintillating nanoparticles (ScNPs).…”
Section: Pdt Using Radioluminescence Lightmentioning
confidence: 99%
“…2-[ 18 F]-Fluoro-2-deoxy-D-glucose ( 18 F-FDG) was the Cerenkov radioactive source used. In the CLT numerical simulation, Cerenkov photons generated by 18 F radioactive source in tissues were simulated by GEANT4, and the transmission process of these Cerenkov photons in tissues was simulated by MOSE (29)(30)(31)(32).…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Cerenkov radiation has attracted a considerable amount of recent research interest for its potential applications in life sciences and engineering, such as in molecular imaging, [35][36][37][38][39][40][41][42][43][44][45][46][47][48] particle detection, [49][50][51][52][53] ionizing radiation quality assurance, and beam monitoring. [54][55][56][57][58] Cerenkov radiation is a visible light emitted from a dielectric medium when charged particles with velocities greater than the phase velocity of the light in that medium, i.e., v > c∕n, pass through it.…”
Section: čErenkov Radiatioňmentioning
confidence: 99%